Study on suppression effect and mechanisms of phosphorus-containing recycling substance on flame propagation of methane/coal dust composite explosion - Li LIU; Xiangbao MENG; Jihe CHEN; Yansong ZHANG; Tong WANG; Lei SHI; Yang WU; Qiyan WU (Meikuang Anquan)
Magnesium ammonium phosphate (MgNH4PO4·6H2O) is a phosphorus-containing blockage commonly found in sewage treatment pipelines. In order to study its suppression effect on the methane/coal dust composite explosion, magnesium ammonium phosphate was subjected to mechanized chemical modification to prepare well-dispersed magnesium ammonium phosphate powder (S-MAP). The improved Hartmann flame propagation system was used to investigate the suppression effect of different mass fractions of S-MAP(20%, 40%, 60%, 80%）on the flame propagation of the methane/coal dust composite explosion. The experimental results indicate that the addition of S-MAP can significantly reduce flame propagation speed, height, and brightness. With the increase of S-MAP addition ratio, the flame propagation height decreased from over 900 mm to 134 mm, and the average flame propagation speed decreased from 8.76 mm/ms to 0.51 mm/s. When the S-MAP addition ratio reached 80%, the entire flame propagation process only presented small flames, which could suppress the propagation of flames; in terms of explosion suppression mechanism, S-MAP decomposition can absorb a large amount of heat, thereby exerting a cooling effect. The intermediate produced by thermal decomposition of S-MAP can adsorb explosion free radicals to block the explosion chain reaction, thereby exerting the effect of adsorbing explosive free radicals. The thermal decomposition products of S-MAP can dilute the concentration of oxygen and combustible gases in the explosion space, and at the same time, the thermal decomposition products can adsorb on the surface of coal dust to isolate the transfer of oxygen and heat, thereby exerting a suffocating effect. The coupling effect of the three suppresses the propagation process of methane/coal dust explosion flames.